Usability of notifications in voice translator’s interface - Vovk, O.; Mendielieva, M.; Chebotaryova, I. (Universidad de Guanajuato Primera Edición, 2025)
Voice user interfaces using AI have opened new opportunities in overcoming the language barrier for travellers on the go in transport hubs such as airports, train and bus stations, ports. Travelling over various distances may involve crossing multiple time zones and then subsequent travel fatigue can there-fore lead to decrease in concentration and alertness, mental and physical performance.
Keywords: traveller; transport hubs